Ripoll Map and the Logic of Its Vignette System with particular Regard to the Balkan Peninsula and Constantinople - Kochanek, Piotr (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
The article consists of three parts. The first part is devoted to the history of research on the map from Ripoll, which was conducted in 1911–2011. The second part of the article contains the text Specimen terrae, which is located on the left and right of the map, as well as analyzes the inscriptions that were inscribed in the southern hemisphere map. The third part is devoted to the northern hemisphere.